Time of day does not influence pacing and performance in a 4 km cycling time trial - Zadow, E. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: Time of day has been shown to impact athletic performance with increases of 10% observed when competing between the hours of 1600 to 2000 h, or within an athlete`s circadian peak window [1]. Physiological factors such as body temperature and hormonal responses display individual circadian rhythms and are believed to be associated with alterations in performance. These factors are also likely to influence the distribution of pace throughout an event, however, we are aware of only one study that has investigated the influence of time of day on pacing [2]. Therefore, the aims of the present study were to investigate the influence of time of day on pacing selection within a 4 km cycling time trial. Methods: Fourteen trained male cyclists (age: 38.9 ± 10.7 y, weight: 77 ± 9 kg, height: 181 ± 7 cm, VO2max: 64.5 ± 8.0 ml/kg/min) performed five 4 km cycling TTs on their own bicycle fitted to a cycle trainer (KICKR: Wahoo Fitness, Atlanta, GA) over five different times of the day (0830, 1130, 1430, 1730 and 2030 h). All trials were completed in a randomised order with each trial separated by a minimum of two and a maximum of seven days. Pacing was assessed through the collection of power, cadence, heart rate and oxygen consumption at 1 km averages throughout each TT. Ratings of perceived exertion (RPE: 6-20) and effort (VAS: 0-10) were collected immediately post TT. Power, cadence, heart rate and oxygen consumption were analysed using two-way repeated measures analysis of variance (Time of Day x distance). RPE and effort were analysed using a repeated measures analysis of variance. Results: No differences in overall average power output, cadence and total time were observed between time trials performed at 0830, 1130, 1430, 1730 and 2030 h (p>0.05). Average heart rate and oxygen consumption remained similar and showed no significant differences between trials (p>0.05). No differences in pacing were observed between the 4 km time trials when performed at 0830, 1130, 1430, 1730 and 2030 h (p>0.05). Conclusion: When assessed at 0830, 1130, 1430, 1730 and 2030 h, the time of day did not influence pacing and performance within a 4 km time trial. The findings from this study may have implications for the testing and monitoring of athletic performance using trials of a similar distance.